التنمية البشرية المستدامة : مفاهيم التكوين وأبعاد التمكين (العراق أنموذجاً) (المجلة العراقية للعلوم الاقتصادية, 2018)
the term sustainable development Acquired interest in "global" after the report (Our Common Future), prepared by the World Commission on Environment and Development in 1987, as was the drafting of the first definition of sustainable development as (those development that meets the needs of the present generation without compromising the ability of future generations to meet their needs) Trying to research that explores the dimensions of the concept through a historical perspective of the development all the way "to achieve the elements of sustainability, which keep for the next generation networking opportunities and enjoy the achievements of the current generation, then moves on research towards opportunities of empowerment achieved by the (sustainable human development and the means or its rights), while the busy hub recent issues of human development in Iraq, according to the "vision (actually and hoped). The adoption of Iraq for the project to grow a sustainable requires a change "systematically" to the path of development, to confirm many of the contemporary issues and according to the "principle (rights: the means and goal), and the turning point that must begin to embrace the philosophy of economic take into account the privacy of the Iraqi experience, supported legislative efforts more careful" the openness of experience to the world outside, and preceded by an effort "to see a political strategy capable of achieving the security requirement of various kinds and deal with the scientific and cultural issues, social, environmental and technological